Olfactory effects of a hypervariable multicomponent pheromone in the red-legged salamander, Plethodon shermani - Wilburn, Damien B. (PLoS One, 2017)
Chemical communication via chemosensory signaling is an essential process for promoting and modifying reproductive behavior in many species. During courtship in plethodontid salamanders, males deliver a mixture of non-volatile proteinaceous pheromones that activate chemosensory neurons in the vomeronasal epithelium (VNE) and increase female receptivity. One component of this mixture, Plethodontid Modulating Factor (PMF), is a hypervariable pheromone expressed as more than 30 unique isoforms that differ between individual males—likely driven by co-evolution with female receptors to promote gene duplication and positive selection of the PMF gene complex. Courtship trials with females receiving different PMF isoform mixtures had variable effects on female mating receptivity, with only the most complex mixtures increasing receptivity, such that we believe that sufficient isoform diversity allows males to improve their reproductive success with any female in the mating population. The aim of this study was to test the effects of isoform variability on VNE neuron activation using the agmatine uptake assay. All isoform mixtures activated a similar number of neurons (>200% over background) except for a single purified PMF isoform (+17%). These data further support the hypothesis that PMF isoforms act synergistically in order to regulate female receptivity, and different putative mechanisms are discussed.